Heavy Metal Content and Spatial Distribution to Determine the Water Pollution Index in Depapre Waters, Papua, Indonesia - Hamuna*, Baigo; Tanjung, Rosye Hefmi Rechnelty (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2020)
A determination of water quality should be conducted as a reference to determine the status of pollution in waters. This study aims to determine the content and distribution of several heavy metals and to determine the pollution index of those heavy metals in Depapre waters, Jayapura Regency, Papua. The sampling of seawater was conducted in October 2017 at five observation stations. The results were then compared to the quality standards of seawater for marine biota based on the Decree of the Minister of Environment No. 51 year 2004. Heavy metal concentrations in the seawater samples were analysed using Atomic Absorption Spectrophotometer (AAS). The results showed that concentrations of Cd, Pb, Cu, and Zn ranged between 0.00-0.003 mg/l, 0.001-0.005 mg/l, 0.464-0.600 mg/l, and 0.003-0.008 mg/l, respectively. Mercury was not detected because its concentration was lower than the detection limit of the tool used. The Hg, Pb, and Zn concentrations fell within the concentration limits specified in the quality standards of seawater for marine biota, whereas the Cd concentrations at stations 1, 2, and 4, and Cu concentrations at all observation stations exceeded the limits specified in the quality standards of seawater for marine biota. Based on the water pollution index, all observation stations fell into the moderately polluted category with a pollution index range of 6.94-7.34. The Cu concentration was the biggest contributor to a high pollution index in the Depapre waters, Jayapura Regency. Keywords: Depapre waters; heavy metals; water pollution index; water quality standard *Corresponding author: Tel.: +62 821 9980 1101 E-mail: bhamuna@yahoo.com.sg